2014
DOI: 10.1371/journal.pone.0089422
|View full text |Cite
|
Sign up to set email alerts
|

RAGE Controls Activation and Anti-Inflammatory Signalling of Protein C

Abstract: AimsThe receptor for advanced glycation endproducts, RAGE, is a multiligand receptor and NF-κB activator leading to perpetuation of inflammation. We investigated whether and how RAGE is involved in mediation of anti-inflammatory properties of protein C.Methods and ResultsWe analyzed the effect of protein C on leukocyte adhesion and transmigration in WT- and RAGE-deficient mice using intravital microscopy of cremaster muscle venules during trauma- and TNFα-induced inflammation. Both, protein C (PC, Ceprotin, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Several differences between MS patients and HI in PC correlation with sICAM1, sNCAM, and sVAP1 concentrations support dysregulation, associated with the MS disease, of the adhesion molecules and PC pathways. The absence of correlation between PC and sICAM and sNCAM in MS patients could be reflected in a decreased inhibition of leukocyte adhesion and transmigration (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several differences between MS patients and HI in PC correlation with sICAM1, sNCAM, and sVAP1 concentrations support dysregulation, associated with the MS disease, of the adhesion molecules and PC pathways. The absence of correlation between PC and sICAM and sNCAM in MS patients could be reflected in a decreased inhibition of leukocyte adhesion and transmigration (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Among hemostasis components, PC has coagulation inhibitor activity and also anti-inflammatory and cell protective properties (6). Activated PC might inhibit leukocyte adhesion and transmigration, downregulating endothelial expression of intercellular adhesion molecule-1 (ICAM1) and vascular cell adhesion molecule-1 (VCAM1) (7,8). In MS-related vascular changes, circulating soluble (s) forms of cell adhesion molecules (CAMs) can result from activated membranes shedding in response to endothelial damage (9).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work by our lab has shown that pulmonary RAGE levels do not change in mice challenged with allergen (20). RAGE activation, however, is thought to induce NF-κB nuclear translocation and amplification of downstream signaling pathways (65, 66), including a number of which promote expression of adhesion molecules such as VCAM-1 (67) and ICAM-1 (68). Two studies exploring the relationship between RAGE and ICAM-1 expression on endothelial cells demonstrated complementary roles for ICAM-1 and RAGE in mediating leukocyte adhesion to endothelium (69, 70).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that LXR activation may enhance TM activity via the TM-thrombin-PC system. Activated TM simultaneously binds to thrombin and PC to form a complex on the surface of endothelial cells, which expresses the endothelial cell PC receptor (EPCR) (31)(32)(33). APC binds with EPCR to downregulate the production of inflammatory cytokines (34).…”
Section: Discussionmentioning
confidence: 99%